2012
DOI: 10.1136/gutjnl-2011-301551
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising enterocolitis is characterised by disrupted immune regulation and diminished mucosal regulatory (FOXP3)/effector (CD4, CD8) T cell ratios

Abstract: Background Necrotising enterocolitis (NEC) is the most common gastrointestinal emergency in premature infants. Immaturity of gastrointestinal immune regulation may predispose preterm infants to NEC as FOXP3 T regulatory cells (Treg) are critical for intestinal immune homoeostasis. Objective To investigate the hypothesis that abnormal developmental regulation of lamina propria Treg would define premature infants with NEC. Design Lamina propria mononuclear cell populations from surgically resected ileum from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(148 citation statements)
references
References 47 publications
8
134
0
Order By: Relevance
“…[6][7][8] Altered control of intestinal bacteria in adults can also result in intestinal inflammation and carcinogenesis. 9 Mouse models for intestinal inflammation have revealed several key factors that are involved in maintenance of homeostatic interactions of the host with intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Altered control of intestinal bacteria in adults can also result in intestinal inflammation and carcinogenesis. 9 Mouse models for intestinal inflammation have revealed several key factors that are involved in maintenance of homeostatic interactions of the host with intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that NEC usually occurs at least a week after birth and after the initiation of enteral feedings is consistent with the idea that the adaptive immune system is also of significance. In a recent human study, premature infants with NEC were shown to have a significantly reduced ratio of T regulatory cells (Tregs) to effector T cells (CD4 + and CD8 + , Teffs) compared to gestational age-matched controls (8). Furthermore, adoptive transfer of Tregs harvested from adult rats have been shown to protect NEC-induced pups against severe intestinal damage (9).…”
mentioning
confidence: 99%
“…Innate and adaptive immune responses are activated after hypoxic ischemic injury, leading to brain inflammation, perpetuated by eventual perinatal infection and inflammation [82]. A robust cerebral immune response, characterized by an imbalance between the pro-inflammatory Th1/ Th17-and the anti-inflammatory Th2/Treg-type responses, has been documented in animal models of white matter injury [35] (Table 1).…”
Section: Periventricular Leukomalacia (Pvl)mentioning
confidence: 99%
“…Moreover, following intrauterine inflammation, the fetal Th1/Th2 ratio shifts towards Th1 cells, with a corresponding increase in interferon-gamma (IFN-γ) [33]. Interestingly, several neonatal diseases are characterized by a pro-inflammatory state due to excessive pro-inflammatory lymphocyte subsets (Th1, Th17) and deficient representation in Tregs [34][35][36] (Table 1).…”
Section: The Neonatal Immune System Is Immature and Incapable Of Manamentioning
confidence: 99%
See 1 more Smart Citation